歯科CTの過去, 現在, 未来 - 勝又, 明敏 (日本口腔外科学会雑誌, 2012)
Today, CT is one of the most important methods of radiological examinations in dentistry. The clinical application of CT starts from the field of oral surgery in the diagnosis of tumorous lesions. Medical CT scanners were large and expensive systems designed for whole-body scanning at a high speed. They were not suited for dentistry, where cost considerations were important, space was often at a premium, and scanning requirements were limited to the head. The advent of arm-type cone beam CT（CBCT） has paved the way for the general dentist to own CT. Moreover, clinical application of surgical simulation and navigation system with 3D CT imaging is getting popular. However in compare with medical whole-body C T, dental CBC T has several disadvantages in the characteristics of density resolution. These are projection data discontinuity related artifact, x-ray beam hardening phenomenon, halation of x-ray detector, and so on. Development of high-speed photon counter type detector based small and inexpensive dental CT scanners has been eagerly anticipated.